2018
DOI: 10.1016/j.ijnss.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotional labor and competency on job satisfaction in nurses of China: A nationwide cross-sectional survey

Abstract: Objectives This study aimed to explore the status of job satisfaction, emotional labour, core competencies and job stress and the associations of emotional labour and core competencies with the job satisfaction of nurses in China. Methods Data were collected by using a self-designed general information questionnaire, a job satisfaction questionnaire (McCloskey/Mueller Satisfaction Scale), a nurse emotional labour questionnaire, the Competency Inventory for Registered Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 26 publications
(27 reference statements)
6
68
1
2
Order By: Relevance
“…In this study, nurse managers had higher JS than clinical nurses. This result is similar to other studies (Suárez et al ; Wu et al ). Nurse managers have different working conditions than clinical nurses.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In this study, nurse managers had higher JS than clinical nurses. This result is similar to other studies (Suárez et al ; Wu et al ). Nurse managers have different working conditions than clinical nurses.…”
Section: Discussionsupporting
confidence: 93%
“…According to Hochschild, the management of emotions requires effort that can result in undesirable consequences, such as unpleasant employees and burnout. Other studies have shown statistically significant results in the positive direction between deep acting and JS (Chou et al ; Wu et al ). This may be because, as suggested by Dogan & Sigri (), nurses who work in an environment shaped by emotional behavioural rules likely encounter fewer problems.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations